Afectación de la cuenta sueldos y salarios en los estados financieros de la empresa Desarrollo Agrícola C.A. durante el periodo 2021. - Carranza Cevallos, Cynthia Cristina (2022)
The present case study developed has allowed us to know in detail the problems faced by Desarrollo Agrícola C.A. due to the non-affiliation of a group of workers. Affiliation to social security is a duty that employers have with their collaborators from the first day of work, according to Article 32 of the Constitution of the Republic of Ecuador, the state guarantees this right that supports good living. It refers in the development of this case study, that the company has a total of workers, whose jobs are from the executive, administrative and agricultural work staff. Of this totality, a number of collaborators among the aforementioned positions have a social security affiliation, and others do not, it should be noted that the company pays all its employees reserve funds, vacations, bonuses, overtime, thirteenth and fourteenth remuneration. The techniques applied in the development of this research are surveys and interviews, in this way the sources of information are primary, additional secondary sources of research are used, given this, the instrument used for the survey is the questionnaire and for the interview is the interview guide.